2020
DOI: 10.1186/s12983-020-00376-8
|View full text |Cite
|
Sign up to set email alerts
|

Bigger doesn’t mean bolder: behavioral variation of four wild rodent species to novelty and predation risk following a fast-slow continuum

Abstract: Background Understanding how wild species respond to novel situations with associated risk can provide valuable insights for inter-specific behavioral variation and associations with pace-of-life (POL). Rodents, a globally distributed and diverse taxonomic group, have been the subjects of countless studies emulating risky situations. Controlled laboratory experiments with a focus on wild-caught species provide the opportunity to test fine-scale behavioral responses to contexts of risk with ecol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 85 publications
(158 reference statements)
0
2
0
Order By: Relevance
“…This suggests that abundance was more important than size in prey selection (Charter et al, 2007). It has also been suggested that owls prefer smaller rodents to heavier ones (Trejo & Guthmann, 2003), probably because smaller species spend more time exploring and foraging, hence being more exposed (Best et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that abundance was more important than size in prey selection (Charter et al, 2007). It has also been suggested that owls prefer smaller rodents to heavier ones (Trejo & Guthmann, 2003), probably because smaller species spend more time exploring and foraging, hence being more exposed (Best et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the post treatment, capturability could have been lower because rodents were not under an immediate predator threat, so they were not compelled to seek shelter. In the first phase, capturability was higher than the post treatment, which could be because traps were novel objects and O. longicaudatus could have been exploring these devices to assess their risks [ 67 , 68 , 69 ]. O. longicaudatus is considered a scansorial species [ 70 ] but it frequently forages on the ground and explores novel sources of food [ 71 ].…”
Section: Discussionmentioning
confidence: 99%